High‐Density Lipoproteins: Structure, Metabolism, Function and Therapeutics. By Anatol Kontush and M. John Chapman. Issue 4 (25th January 2013) - Sviridov, Dmitri
<x xml:space="preserve">Abstract</x> Wiley, Hoboken 2012. 648 pp., hardcover, $135.00.—ISBN 978‐0‐470‐40821‐6<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>